Task force of Nanga Badau cross-border post as Indonesia’s defense diplomacy instrument in Indonesia-Malaysia border - Aniroso, Hartono; -, Sutiono; Surryanto,; Thomas Gabriel, (Technium Social Sciences Journal, 2020)
The Indonesia-Malaysia border has been a part of cooperation since Malaysia's independence in 1957. The development of a dynamic strategic environment such as boundary violations followed by trans-national crime has made no country immune to international crime. On the other hand, border security efforts require the cooperation of the two countries. Whereas cooperation between the two countries requires clarity of boundaries. The border protection measures carried out by patrol, maintenance and border security are defense efforts through Military Operations Other Than War. According to Cottey and Foster, defense diplomacy is an effort to prevent conflict carried out by the military in the form of diplomacy carried out both in peacetime and in wartime. Delimitation is known in securing the boundary, namely the political efforts of two countries that agree to a boundary based on an agreement on paper related to existing documents. then demarcation is the effort of two countries to establish national borders by establishing border stakes. Finally, the administrative process, which is the effort of the two countries in managing the border region, to become a common and mutually beneficial space and at the same time secure the borders of the two countries. What is the relevance of border security as an instrument of defense diplomacy? How is defense diplomacy carried out as part of a defense strategy? To analyze the research questions above, a qualitative-descriptive research method was conducted. As a result, as Military Operations Other Than War, border security is an inevitable part of border diplomacy in the context of preventing conflict and maintaining Indonesian sovereignty as part of Indonesia's defense. Diplomacy is carried out in informal ways within the scope of expert working groups in the field through military to military contact, and TNI relations with civil society both Indonesia and Malaysia. Expert Working Group such as the efforts of experts from the Directorate of the Indonesian Army Topography and Malaysian topographers consisting of civilians who are assisted by the Malaysian Army Force into defense diplomacy media. The relationship established by TNI officers with tribal leaders in the border region became a persuasive diplomatic effort to further strengthen cooperation between the two parties.